Hate as evaluation: A discourse analysis of language and emotion in Youtube political comments - Khotimah, Khusnul; Fanani, Achamd (Universitas Ahmad Dahlan, 2026)
This study examines the linguistic and psychological dynamics of hate speech in Indonesian political discourse on YouTube by analyzing user comments on a CNN Indonesia talk show discussing Gibran Rakabuming Raka. Using a qualitative approach grounded in appraisal-based discourse analysis, the study analyzes 1,534 comments to explore how evaluative language constructs moral conflict in online political communication. The findings reveal that hate speech is predominantly expressed through negative judgment, which accounts for 45% of the data, followed by contractive engagement strategies that restrict dialogue (44%) and intensified graduation that amplifies emotional force (12%). These linguistic patterns indicate that political disagreement is frequently framed as moral condemnation rather than rational debate. The study further demonstrates that such evaluative strategies are closely linked to psychological processes, including moral conviction, group identity signaling, and emotional contagion, which collectively intensify polarization in digital spaces. By integrating linguistic analysis with psychological perspectives, this research highlights hate speech as a form of moralized discourse that escalates affective conflict. The study concludes by recommending digital literacy interventions that extend beyond content moderation to address underlying evaluative and emotional processes, with the aim of fostering empathy, critical reflection, and more constructive online political engagement.